Rhetorical Stages in Ustadz Abdul Somad's Lecture "Strengthening the Spirit of Unity" on YouTube - Ningsih, Pera Julia; Asnawi, Asnawi (Language Circle: Journal of Language and Literature, 2024)
Delivering lectures requires language skills and a language style known as rhetoric. Rhetoric in lectures functions to influence other people to confirm and follow what is said. The aim of the research is to describe and analyze the rhetorical stages in Ustadz Abdul Somad's lecture "Strengthening the Spirit of Unity" on YouTube.  This research is called qualitative research using descriptive methods.  The primary data source in this research is a video recording of Ustadz Abdul Somad's lecture on his YouTube account which was published on July 10 2024 with the title "Strengthening the Spirit of Unity". The data collection technique used in this research is the watch, listen and note technique. Data analysis is carried out by collecting data, reducing data, presenting (displaying) data, and drawing conclusions/verification. The research results show that Ustadz Abdul Somad has applied 5 stages of rhetoric in delivering his lecture about strengthening the spirit of monotheism, namely: discovery, arrangement, style, delivery, and remembering. Ustadz Abdul Somad is known for delivering identical lectures using Malay and being humorous. In delivering lectures he also always delivers lectures with tafsir and hadith.